2023
DOI: 10.1109/access.2023.3313113
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying Detection and Severity Determination Model

Mohammed Hussein Obaid,
Shawkat Kamal Guirguis,
Saleh Mesbah Elkaffas

Abstract: Some teenagers actively participate in cyberbullying, which is a pattern of online harassment of others. Many teenagers are unaware of the risks posed by cyberbullying, which can include depression, self-harm, and suicide. Because of the serious harm it can cause to a person's mental health, cyberbullying is an important problem that needs to be addressed. This research aimed to develop a technique to identify the severity of bullying using a deep learning algorithm and fuzzy logic. In this task, Twitter data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The final set of tests is performed to compare the difficulty of the proposed system. In other terms, the utilization of computer resources by a program is explored using the same citations as discussed in our prior publication [7]. The duration taken for one complete cycle of the dataset in question is detailed in Table 5 within this investigation, which showed that the required times were 493 sec, 21 sec, and 814 sec for Twitter, Instagram, and Facebook, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final set of tests is performed to compare the difficulty of the proposed system. In other terms, the utilization of computer resources by a program is explored using the same citations as discussed in our prior publication [7]. The duration taken for one complete cycle of the dataset in question is detailed in Table 5 within this investigation, which showed that the required times were 493 sec, 21 sec, and 814 sec for Twitter, Instagram, and Facebook, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The study presents the creation of an LSTM deep learning detection model capable of identifying cyberbullying content in user comments across three distinct social media platforms in real-time. The experimental setup for the new dataset closely follows the methodology outlined in a prior publication [7]. in an attempt to solve the limitation, allowing us to examine how well the suggested model performs on the chosen datasets and how adaptable it is to other datasets.…”
Section: Introductionmentioning
confidence: 99%
“…The study [18] involves the utilization of a deep learning algorithm in conjunction with fuzzy logic to analyze 47,733 comments from Twitter, obtained from Kaggle. The methodology includes processing these comments using Keras embeddings and classifying them with a four-layer LSTM network.…”
Section: Related Workmentioning
confidence: 99%
“…(2024) [17] proposed a method using a CNN to detect cyberbullying incidents on Instagram, demonstrating the capacity of deep learning models to discern intricate patterns in multimedia-rich content. Long Short-Term Memory (LSTM) networks, a type of RNN, have been employed for sequential modeling, enabling the understanding of temporal dynamics in cyberbullying conversations [18] . Deep learning models showcase a high degree of sophistication in understanding context and semantics, making them well-suited for cyberbullying detection tasks.…”
Section: Existing Approaches To Cyberbullying Detectionmentioning
confidence: 99%